Developing contraceptive services for immigrant women postpartum - a case study of a quality improvement collaborative in Sweden - Helena Kilander; Maja Weinryb; Malin Vikström; Kerstin Petersson; Elin C. Larsson (BMC, 2022)
Abstract Background Immigrant women use less effective contraceptive methods and have a higher risk of unintended pregnancies. Maternal health care services offer a central opportunity to strengthen contraceptive services, especially among immigrants. This study aimed to evaluate a Quality Improvement Collaborative QIC. Its objective was to improve contraceptive services for immigrant women postpartum, through health care professionals' (HCPs) counselling and a more effective choice of contraceptive methods. Methods The pilot study was designed as an organisational case study including both qualitative and quantitative data collection and analysis. Midwives at three maternal health clinics (MHCs) in Stockholm, Sweden participated in a QIC during 2018-2019. In addition, two recently pregnant women and a couple contributed user feedback. Data on women's choice of contraceptive method at the postpartum visit were registered in the Swedish Pregnancy Register over 1 year. Results The participating midwives decided that increasing the proportion of immigrant women choosing a more effective contraceptive method postpartum would be the goal of the QIC. Evidence-based changes in contraceptive services, supported by user feedback, were tested in clinical practice during three action periods. During the QIC, the proportion of women choosing a more effective contraceptive method postpartum increased at an early stage of the QIC. Among immigrant women, the choice of a more effective contraception increased from 30 to 47% during the study period. Midwives reported that their counselling skills had developed due to participation in the QIC, and they found using a register beneficial for evaluating women's choice of contraceptive methods. Conclusions The QIC, supported by a register and user feedback, helped midwives to improve their contraceptive services during the pregnancy and postpartum periods. Immigrant women's choice of a more effective contraceptive method postpartum increased during the QIC. This implies that a QIC could increase the choice of a more effective contraception of postpartum contraception among immigrants.